EFFECT OF SUB -LETHAL DOSE OF SOME INSECT GROWTH INHIBITORS ON SOME PHYSICAL FEATURES OF WINGS CUTICLE OF AMERCINCA COCKROACH PERIPLANETA AMERICANA - & Al- Mallah, Mansor (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The results of treating the last nymphal instar of periplaneta americana by sub-lethal dose (o.1 ml of 0.2%) of Azadirachtin . Lufenuron and Methoxyfenozide . on some physical features of adults wings produced from treated nymphs. The results revealed asignificant variation in wings cuticle resistance to electrical current between treatment and control. The control treatment showed a highest degree of electrical resistance in front and hind wings of right and left direction and reached 157.89 . 170.89 . 134.33 . and 170.89 omh/m respectively. The electrical resistance of wings cuticle in treatments were varied according to the kinds of insect growth in hibitors . The same treatment also exhibited a varied degree of wings absovption to ultra violet and infrared rays at different wave length according to the kind of IGR and wave length in comparison with control treatment . these results confirmed that IGR changed the texture and components of the treated wings with IGR.